Analysis of Factors that Influence Recruitment and Selection Process - Ninawati; Fransiska Liska; Veronika Tiara; Yusawinur Barella (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Effective Human Resources (HR) management is the key to the success of everycompany in achieving its strategic goals. In this context, recruitment, selection,and placement of employees play an important role as the first process thatdetermines the quality and performance of a company's workforce. This studycovers recruitment, selection, factors influencing selection, as well as therecruitment and selection process. The data collected is analyzedcomprehensively to identify patterns, trends, and relationships between therecruitment and selection process and its factors, as well as placement inorganizational performance. The results of this study are intended to providevaluable insights for human resource managers. The practical implications of thisresearch will lead to the development of selection factors, more accuraterecruitment and selection processes, and more targeted staff placement, which inturn will improve overall organizational performance.